Applications of density functional theory to heavy metal binding to magnetic-cored dendrimer. (October 2019) - Kim, H-R; Boukhvalov, D W; Park, J-W
Abstract: Magnetic-cored dendrimer (MD) is a nano-material composed with the magnetite nanoparticle in the core and dendritic branches developed on the surface of the core. Due to the unique structure and magnetic property of the MD, it has been studied for various environmental applications including the adsorption. With a large number of the terminal group, the poly (amidoamine) dendrimer provides many possible binding positions to various kind of contaminants. It has been reported that the heavy metal adsorption shows different affinity depending on heavy metal species in the aqueous phase. In this study, the MD was synthesized and their binding efficiency experimented with four different dissolved heavy metals of Pb (II), Cu (II), Zn (II), and Cr (VI). The maximum adsorption capacity of heavy metal was in the following order: Pb 2 + > HCrO4 - > Zn 2 + > Cu 2 +. The interaction between the MD and the targeted heavy metal was calculated using the density functional theory (DFT). A pseudo-potential code SIESTA model was used. The calculated enthalpy of each metal indicated an agreement with the experimental result. A specific binding position and energies of different heavy metal species were confirmed through DFT calculations. The calculated enthalpy demonstrates structural and dynamical characteristics between MD and heavy metals. The binding preference of MD to a different kind of heavy metal provides useful information for the environmental applications.